Budgeting And Emotional Exhaustion In Covid-19 Pandemic: Survey From Indonesia - Mardiana Mardiana; SeTin SeTin (Jurnal Akuntansi, 2023)
Management control practices will change in response to the global crisis. This study aims to investigate the behavioural impacts of adjustments in budget control brought on by the worldwide crisis, particularly during the transition to the COVID-19 pandemic. This quantitative study employs a questionnaire survey approach with a sample of 96 managers from West Java manufacturing enterprises. The results of the study show that the negative impact of the Covid-19 pandemic transition period is positively related to budget tightening, tightening budget control is positively associated with role conflict, enabling budget design can reduce the impact of budgetary tightness on role conflict, and role conflict is positively related to emotional exhaustion of budget holders. This study contributes to the body of knowledge on management control, particularly the budget, which sheds further light on how budgeting procedures change in times of crisis and what happens to employees as a result of those changes.